Signal to noise ratio of the image of the star Capella with respect to the CCD temperature / Rafidah Sarnin - Sarnin, Rafidah (2007)
This study focused on signal to noise ratio of the image of the star Capella with respect to CCD temperature. In this research we used Meade 8" LX200 GPS Telescope, SBIG ST-8XME CCD Camera and computer to link the telescope and CCD camera. We also used the computer software such as AIP Software to calculate signal to noise ratio and Sky6 Software to determine the star location and time. Signal comes from the number of photon striking the detector inside the CCD camera and liberated as electron. Noise is the uncertainty of the signal. It is present in all signal. There are some sources of noise which are dark current, bias current, bias current and thermal current. Once we grab an image, the image was recorded because the CCD receives the signal. The image looks grainy because of the noise and this is called raw image. Signal to noise ratio is the measure of the quality of the image. The better the image quality is the higher the signal to noise ratio of the star image. At lower temperature of the CCD camera from the noise of the dark current was reduced and signal to noise ratio is higher. Besides that, we also computed the magnitude of the star to determine the degree of the star brightness. The magnitude of the star is lower at lower temperature of the CCD. The lower the magnitude, the star is brighter. Finally, the image quality of the star is better when signal to noise ratio is high and the noise from dark current is reduced. The magnitude of the star is smaller at lower temperature.